Analisis Pengaruh Work Life Balance dan Beban Kerja Terhadap Kinerja Karyawan melalui Kepuasan Kerja (Studi Kasus Pada PT Nusantara Building Industries Demak) - Firdaus, Nada Nisrina; Sijabat, Rauly; Indiworo, Rr. Hawik Ervina (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study investigates the influence of work life balance and workload on employee performance with job satisfaction as a mediating variable at PT Nusantara Building Industries Demak. The research employs a quantitative explanatory approach and uses a total sampling technique involving 171 employees. Data were collected using a structured questionnaire and analyzed through Structural Equation Modeling (SEM) with AMOS version 28 to test direct and indirect relationships between variables. The findings indicate that work life balance has a positive and significant effect on both job satisfaction and employee performance. Employees who are able to balance work demands with personal life tend to feel more satisfied and perform better in their roles. In contrast, workload shows a positive effect on job satisfaction but does not significantly influence employee performance. Furthermore, the study reveals that job satisfaction does not significantly mediate the relationship between workload and employee performance, nor does it mediate the relationship between work life balance and employee performance. These results highlight the importance of maintaining work life balance as a strategic factor for improving satisfaction and performance within the company. Although workload does not directly decrease performance, it must still be managed effectively to prevent declines in job satisfaction. The implications of this study encourage companies to develop work policies and a supportive organizational climate that enable employees to achieve balance between work and personal life, thus optimizing long-term performance outcomes.